Istikhdām Ṭarīqah Drill Bi aṣ-Ṣuwar aṡ-Ṡābitah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Saiṭarah al-Mufradāt al-`Arabiyyah (Baḥṡ Tajrībī Fī al-Madrasah aṡ-Ṡānawiyyah Fajar Hidāyah Bi Aceh Besar) - Muhammad Muhammad; Zulhelmi Zulhelmi (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Vocabulary is the most important element in learning Arabic. In teaching this lesson, teacher must use a suitable teaching methods and image media to achieve the goals of study, unless it will be failed. For instance, some second grade students of junior high school in Fajar Hidayah Islamic boarding school, they studied vocabulary but some of them could not apply in oral or written Ta'bir. The main problem is due to the teacher had not practice suitable methods yet in teaching vocabulary. In order to solve the problem, the researcher applied method driil and image media in teaching vocabulary to the students of junior high school in Fajar Hidayah Islamic boarding school. The purpose of this research is to know the student's response to vocabulary learning by applying drill methods and image media and the effectiveness of its application to improve the ability of students in the study of vocabulary. The used method was quasi experimental designs. The study population is all students of the junior high school Fajar Hidayah and samples are second graders amounting to 22 students. The results showed that students ' responses to vocabulary learning by applying drill methods and image media were very good and the implementation was effective to improve the students ' ability to control the mufradat in the integrated Islamic School of Dawn Hidayah, evidenced by the T-count value greater than T-table.